The Effect of Music Therapy and Murottal Therapy on Anxiety Patient In The Intensive Care Unit: A Case Report: Pengaruh Terapi Musik dan Terapi Murotal pada Pasien Ansietas di Ruang Perawatan Intensif: Case Report - Dina Lestari; Hanny Handiyani; Tuti Nuraini; Dewi Gayatri (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Anxiety is an emotion that is often experienced by patients who admitted to the ICU. Anxiety occurs due to the ofenvironmental stressors, multiple invasive actions, feelings of loneliness and fear of death. There are severalcomplementary therapies that are feasible to be administered to reduce anxiety levels, such as music therapy and murotaltherapy. The purpose of this study was to identify the application of music therapy and murotal therapy to reduce anxietyin patients treated in the intensive care. The study design used a case study on 1 respondent with the criteria of patientsbeing treated in the ICU > 48 hours on a ventilator, with compos mentis awareness. This study was conducted for 5 days.The results showed that there was a decrease in the level of anxiety of patients who were treated before and after givenmusic therapy and murotal therapy . Before the intervention was applied, Mrs. I anxiety score is 86 (moderate) and afterbeing administered for 5 days, the anxiety of the respondent decreased with score of 62 (mild). The pain level in Mrs. Ibased on Behavior Pain Scale (BPS) has decreased from scale of 6 (moderate) to scale od 3 (mild). Based on these twomeasuring instruments, the vital signs which previously rose within the upper normal limit decreased to within the normalrange. Based on the data this intervention is considered effective in relieving anxiety, pain, and making vital signs stablewithin the normal range experienced by critical care patient.